(untitled) (Práxis Educativa, 2020)
This study analyzed the presence and reinvention of Paulo Freire’s thinking on the policies and practices of teacher education in Youth and Adult Education developed within the scope of the Regional Education Directorate Pirituba-Jaraguá, São Paulo, between 2013-2016. It was assumed that elements of the teacher education proposal put into practice during Paulo Freire’s Administration (1989-1992) have been continued and recreated in the Municipal Education Network of São Paulo, subjected, however, to conditions that gain or lose strength according to the political commitment assumed by the public administration. The qualitative research adopted the following methodological procedures: document analysis, interviews and participant observation. The theoretical framework relied mainly on contributions from Paulo Freire, Vitor Paro and Rubens de Camargo. The findings confirmed the initial hypothesis, pointed out conditions involved in the resurgence of Freirean assumptions in teacher education and demonstrated the feasibility of reinventing Freire’s legacy in policies and public networks of education. Keywords: Paulo Freire. Education policy. Teacher education.